Antibacterial Activity of Essential Oil from Rosemytle Leaves (Rhodomyrtus tomentosa (Ait.) Hassk) - Salni Salni; Hanifa Marisa (Molekul, 2020)
Rosemytle leaves (Rhodomyrtus tomentosa (Ait.) Hassk) have been used by society to treat various diseases related to bacterial infections, such as dysentery and typhoid fever caused by Shigella dysenteriae and Salmonella typhi, respectively. This study aimed to evaluate the antibacterial activity of essential oils from rosemytle leaves against both bacterias. Extraction was performed with a macerating device using n-hexane, ethyl acetate, and ethanol extracts, sequentially. This study used the agar diffusion method to test the antibacterial activity applied to the essential oils with concentrations of 1000, 500, 250, 125, 62.5, and 31.25 μg/mL. The antibacterial test results showed that n-hexane and ethyl acetate extracts were active against both bacterias while ethanol extract was not. Then, isolates N1 and E1 were produced respectively from n-hexane extract and ethyl acetate extract. The MIC values of both N1 and E1 for S. dysenteriae, and S. typhi were the same, namely 125 μg/mL. Isolate N1 was an essential oil containing menthol (59.60%), caryophyllene (25.77%), and cubenol (14.63%) while isolate E1 was an essential oil containing (73.93%), pentanone (8.30%), alpha calacorene (7.58%), and calacorene (3.78%). Rosemytle leaves have the potential to be developed as a drug to treat dysentery and typhoid fever.